TIPE GABUNGAN MENDOMINASI JENIS PRE MENSTRUAL SYNDROME (PMS) PADA MAHASISWI TINGKAT I DAN II PRODI DIII KEBIDANANUNUSA - Nisa’, Fauziyatun (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2018)
Premenstrual syndrome (PMS) is a combination of physical, psychological, and emotional symptoms that relate to the woman’s menstrual cycle. The types of this syndrome can be classified according to its symptoms: type A (anxiety), type H (hyperhydration), type C (craving), type D (depression), and the combination of all mentioned types. The objective of this research was to identify the dominant type of PMS experienced by Diploma-III students Program of Study of Midwifery – Fakultas ilmu keperawatan dan kebidanan UNUSA. This research was descriptive by using the cross sectional design. The population involved 245 Diploma-III students Program of Study of Midwifery - UNUSA in 2015-2016. 152 students were taken as the samples by using the probability sampling technique in which the simple random sampling was used. The data collected by using questionnaires and descriptive analysis . Tthe result showed that 56 students experienced PMS type A; 3 students experienced type H; 16 students experienced type C, and only one student experienced type D; whereas 76 students experienced the combination of all types which was considered as the dominant. The conclusion was that the female students having PMS would not only experience one type of syndrome, but they might also experience various types at the same time. Hence, they are expected to understand their reproductive health and to get clear information and the right solution when having PMS.